"Fat-Rich" (Spindle Cell-Poor) Variant of Atypical Spindle Cell/Pleomorphic Lipomatous Tumor: Striking Mimic of "Classical" Atypical Lipomatous Tumor/Well-Differentiated Liposarcoma. (December 2019) - Creytens, David; Mentzel, Thomas; Ferdinande, Liesbeth; van Gorp, Joost; Van Dorpe, Jo; Flucke, Uta
We report the case of a "fat-rich" (spindle cell-poor) variant of an atypical spindle cell/pleomorphic lipomatous tumor in a 63-year-old female patient presenting with a firm, painless soft tissue mass on the right hip. Atypical spindle cell/pleomorphic lipomatous tumor is a very recently described low-grade adipocytic neoplasm, which occurs predominantly in adults with a predilection for the limbs and limb girdles. In the present case, the diagnosis of an atypical spindle cell/pleomorphic lipomatous tumor was challenging because the tumor was almost exclusively composed of an atypical adipocytic component (resembling "classical" atypical lipomatous tumor/well-differentiated tumor) with only very focal presence of the diagnostic atypical morphologic features (atypical spindle-shaped cells, floret-like multinucleated cells, and "bizarre" pleomorphic [multinucleated] cells). The possibility of a "classical" atypical lipomatous tumor/well-differentiated liposarcoma was ruled out by immunohistochemistry (lack of MDM2 expression and loss of Rb expression) and molecular genetic testing (no amplification of MDM2 and presence of monoallelic deletion of RB1 ). Another interesting morphologic observation in this case was the striking perivascular location of the atypical spindle/pleomorphic cells in some areas (so-called "pericytic mimicry"). To our knowledge, pericytic mimicry has not been reported in the setting of an atypical spindle cell/pleomorphic lipomatous tumor.